1986
DOI: 10.1002/polb.1986.090240303
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Cu2+ catalysts from Cu‐metal polymer or Cu‐oxide/polymer interfaces into isotactic polypropylene

Abstract: Diffusion coefficients of Cu2+ in the form of its carboxylate have been measured in isotactic polypropylene as a function of temperature (90–128°C) and extent of preoxidation. Diffusion take place from the metal catalyst/polymer interface into the bulk polymer. The diffusion is dependent on the extent of preoxidation and temperature but not on the type of catalyst (Cu, CuO, CuO0.67). Analysis of polymer sections for Cu2+ ions was carried out with a selective Cu2+ electrode. Diffusion in isotactic polypropylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Since it has been reported that the higher the temperature, the more easily the carboxylate diffuses in the resin matrix. 6668 The relatively thick interphase layer might be formed by the diffusion of the carboxylate generated at the interface in some high temperature process during manufacturing.
Figure 2.Maps (left) and profiles (right) of height (a) and AFM-IR intensities at 1582 cm −1 (I1582) for carboxylate (b) and 1502 cm −1 (I1502) for epoxyacrylate (c) and the ratio of these intensities (I1582/I1502) (d).
…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been reported that the higher the temperature, the more easily the carboxylate diffuses in the resin matrix. 6668 The relatively thick interphase layer might be formed by the diffusion of the carboxylate generated at the interface in some high temperature process during manufacturing.
Figure 2.Maps (left) and profiles (right) of height (a) and AFM-IR intensities at 1582 cm −1 (I1582) for carboxylate (b) and 1502 cm −1 (I1502) for epoxyacrylate (c) and the ratio of these intensities (I1582/I1502) (d).
…”
Section: Resultsmentioning
confidence: 99%